Effectiveness of Combination Ethanol Extract of Cherry Leaves and Turmeric as Antibacterial Propionibacterium acnes - Rifda, Rifda; Lisdiana, Lisa (LenteraBio : Berkala Ilmiah Biologi, 2022)
Skin tissue infections are caused by microorganisms such as Propionibacterium acnes that can trigger acne. Long-term use as an acne medication and inappropriate doses can increase the incidence of antibiotic resistance. Cherry leaves and turmeric scientifically contain chemical compounds that are antibacterial. This study aims to find out the effectiveness of the combination of cherry leaf and turmeric ethanol extract as an antibacterial of P. acnes. Each extract was obtained by maceration technique using 96% ethanol. Antibacterial activity test used the well-diffusion method. Clindamycin was used as a positive control and DMSO 10% as a negative control. The data was analyzed using Anova One Way followed by Duncan’s test. The concentration use for the combination test was obtained from MIC of the single extract test result. The combination test of extracts with a ratio of 1:3, 2:2, 3:1 resulted in an average inhibition zone of 0.76±0.024 cm; 0.84±0.16 cm; 1.20±0.29 cm. The combination of cherry leaves ethanol extract and turmeric is effective as an antibacterial for P. acnes. The optimal combination in inhibiting the growth of P. acnes is a ratio of 3:1.